(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Phenomenon of musical art considered as one of the conditions needed to create artistic and aesthetic communication that nurtures the growth of a spiritual, moral and harmonious personality. This article focusses on finding new bases for music education. It outlines current music education and points out difficulties that are caused by rapid changes in music culture. Due to these changes, music curriculum must find new starting points. We explored and compared the main ideas about music education in its historical development. We conclude that music education today should be built on music making and listening. It can no longer be based on traditional frameworks because they are not familiar to individuals today. Music education should be based on research, and new ways of teaching and learning musical skills and knowledge should guide its practice.